2019
DOI: 10.3390/ijms20133182
|View full text |Cite
|
Sign up to set email alerts
|

Renin Activity in Heart Failure with Reduced Systolic Function—New Insights

Abstract: Regardless of the cause, symptomatic heart failure (HF) with reduced ejection fraction (rEF) is characterized by pathological activation of the renin–angiotensin–aldosterone system (RAAS) with sodium retention and extracellular fluid expansion (edema). Here, we review the role of active renin, a crucial, upstream enzymatic regulator of the RAAS, as a prognostic and diagnostic plasma biomarker of heart failure with reduced ejection fraction (HFrEF) progression; we also discuss its potential as a pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 252 publications
(344 reference statements)
0
47
0
Order By: Relevance
“…Attenuation of edema and pleural effusion in corin-Tg(i)/DCM mice may be associated with less volume and pressure overload and improved contractile function as a compensatory effect [53]. Reduced edema is also associated with normalization of circulating neprilysin level as reported for patients with HFrEF and in experimental HF [35,52,54] and trend toward down-regulation of renin plasma activity and aldosterone levels [44,47,55,56]. HF continues to increase in incidence and prevalence [1].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Attenuation of edema and pleural effusion in corin-Tg(i)/DCM mice may be associated with less volume and pressure overload and improved contractile function as a compensatory effect [53]. Reduced edema is also associated with normalization of circulating neprilysin level as reported for patients with HFrEF and in experimental HF [35,52,54] and trend toward down-regulation of renin plasma activity and aldosterone levels [44,47,55,56]. HF continues to increase in incidence and prevalence [1].…”
Section: Discussionmentioning
confidence: 94%
“…Transcript levels of GATA-4, a common transcription factor for corin, ANP, and BNP [32] remained unchanged among all three groups (Figure 5g). Systemic activation of the renin-angiotensin-aldosterone system (RAAS) occurs in HF with increased plasma renin activity, angiotensin II, and aldosterone levels [42][43][44][45][46][47]. We reported that systemic RAAS is significantly activated in female mice with DCM starting from Stage B HF [35,36].…”
Section: Effect Of Cardiac Corin-tg(i) Overexpression On Hf Plasma Bimentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental studies have linked elevated plasma renin activity levels in female mice with DCM to accelerated, sex-related deterioration in systolic function, HF progression, and early mortality [27]. While active renin is acknowledged to initiate production of both Ang II and aldosterone [38,43], clinical studies have not rigorously examined plasma renin activity in the pathogenesis of HF [32,34,35,36,37,44]. Active renin concentration was recently suggested as a potential indicator for guiding HF with reduced EF (HFrEF) in addition to BNP and New York Heart Association classification [45].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the development of Stage C HF, which is associated with edema and other biomarker abnormalities, female mice show increased plasma renin activity concentrations [27]. Renin is an enzyme that specifically catalyzes the first and rate-limiting step in the activation of angiotensin II (Ang II) and renin enhances the secretion of aldosterone, which promotes salt and water retention and worsens the development and progression of HFrEF [29,30,31,32]. Plasma renin activity increases with HF stages and varies between patient subsets [27,33].…”
Section: Introductionmentioning
confidence: 99%